Characterization and production of Ceiba pentandra biodiesel and its blends - Silitonga A.S.; Ong H.C.; Mahlia T.M.I.; Masjuki H.H.; Chong W.T. (Elsevier Ltd, 2023)
This paper investigates the opportunity of biodiesel characterization and production from Ceiba pentandra seed oil. The biodiesel production was conducted by two step acid-base transesterification. The process was carried out using acid catalyst (H2SO4) and alkaline catalyst (NaOH). It has been found that the properties of C. pentandra methyl ester fell within the recommended biodiesel standards (ASTM D6751 and EN 14214). Beside, this study also suggests biodiesel-diesel blending to improve the properties of biodiesel such as viscosity, density, flash point, calorific value and oxidation stability. Finally, it can be concluded that this feedstock can be considered as a possible source for biodiesel production. 2013 Elsevier Ltd. All rights reserved.